Lingwistyczny dydaktyzm „Nocy attyckich” Aulusa Geliusza - Wolanin, Hubert (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2009)
The aim of this paper is to examine the didactic value of the Attic Nights from the linguistic point of view, and precisely, from the point of view of Gellius’ teachings on the meanings of words. In this context it has been stated that the author makes his readers aware of new meanings gained by certain words when used in contemporary colloquial idiom, describes and interprets the mechanism which had generated those meanings, evaluates the results of the process of semantic change, and, finally, comments on the way some grammarians assess the usage of certain words in ancient literary texts. In effect, the paper concentrates on the passages where A. Gellius, referring to ancient (archaic and classical) literature, describes the semantic differences occurring in various words, depending on their usage, whether in literary or colloquial language, defines the linguistic mechanism giving rise to colloquial variants of different linguistic items, and presents in a critical light the influence of colloquial language on the way in which interpretation is made of particular words as they occur in literary texts.

The aim of this paper is to examine the didactic value of the Attic Nights from the linguistic point of view, and precisely, from the point of view of Gellius’ teachings on the meanings of words. In this context it has been stated that the author makes his readers aware of new meanings gained by certain words when used in contemporary vulgar language and gives testimony to the process of dissemination and perpetuation of particular semantic variants appearing in colloquial idiom for given words. What is more, he also describes the mechanism which had generated those meanings, and evaluates the results of the process of the semantic changes; in his opinion, the mechanism responsible for the generation of changes in meaning within lexical items, leading up to the establishment of new, colloquial meanings for particular words, is the protracted misuse of language in the mouths of simple and uneducated people. So, he sees consuetudo et inscitia temere dicentium or ignoratio et inscitia improbe dicentium quae non intellegant as a factor giving rise to new, colloquial, and in the same time incorrect meanings of words. And finally, commenting on the way some grammarians assess the usage of certain words, especially in ancient literary texts, he gives some methodological, metalinguistic remarks. In particular, when defending Virgil against the accusation levied be the grammarian L. A. Cornutus that the verb vexare is too weak to be used with reference to Scylla tossing Ulysses’ ship since it is commonly used of the annoyance of smoke or wind or dust, Gellius, referring to the argument of etymology and analogy, stresses that the meaning of a given word as perpetuated in colloquial idiom cannot be treated as a sufficient criterion for the assessment of the correctness of a given usage, especially if that usage appears in literature. Thereby he presents in a critical light the influence of colloquial language on the way in which interpretations are made of particular words as they occur in literary texts. Contemporary speech is shown as a dangerous factor which gives rise to inappropriate approaches to question of value.
Linguistic didacticism in the Noctes Atticae by Aulus Gellius
Keywords: Gellius; linguistics; semantics; linguistic change